Chemical vapor deposition of graphene on prepatterned catalyst - Lin, Xiaotian (My University)
This thesis explores the growth of high-mobility monolayer graphene on copper foils using Chemical Vapor Deposition (CVD), focusing on the influence of surface morphology and grain size of the copper substrate. Graphene’s exceptional electrical, thermal, and mechanical properties make it a promising material for various advanced electronic applications, particularly in the development of graphene field-effect transistors (GFETs). However, achieving high-quality graphene with uniformity and minimal defects remains a significant challenge, primarily due to the variations in the copper substrate’s surface characteristics. In this work, we investigate the correlation between the copper foil’s surface morphology and grain size and the quality of the graphene produced. The study employs low-pressure CVD (LPCVD) with methane as the carbon source, and hot-wall thermal CVD to precisely control the deposition environment. Key factors such as the copper substrate’s crystallinity, smoothness, and catalytic properties are analyzed to optimize the growth process. The self-limiting nature of graphene growth on copper, facilitated by copper’s low carbon solubility, is leveraged to achieve uniform monolayer graphene. This project also includes the prepatterning method as one of the ways of controlling the alignment of nuclei, which is done based on maskless photo-lithography. By using prepatterning, patterned oxidation on copper foils can be achieved, the nucleation of graphene during CVD growth can only happen on the open areas where there’s no oxide layer, which controls the position of nuclei. Furthermore, this research aims to enhance the copper substrate preparation methods to improve graphene’s mobility and overall quality, thus making it more viable for large-scale production. The outcomes of this study could contribute to advancing the scalability of high-performance graphene for industrial applications, particularly in the field of nanoelectronics.